Mythical Character of Space in the Place Legends on the Plateliai Lake - Kaniava, Andrius (Tautosakos darbai, 2024)
Using the place legends stored at the Lithuanian Folklore Archives and the questionnaires from the Collection of the Lithuanian Place Names, the author of the article analyzes folklore related to the Plateliai Lake (in Plungė District) and its segments, including islands, peninsulas, and shallows. Having systematized a number of place legends related to the lake, the author discerns three themes that are further analyzed in the article, namely: the appearing of the Plateliai Lake and several lakes connected underground, the underwater world of Plateliai (the lake demanding sacrifices), and the image of the Plateliai Queen. Applying the concept of the mental landscape and the current research on placelore, he reveals the mythical character of the Plateliai Lake and its surrounding space. Special attention is paid to the way that various segments of the lake are depicted in place legends. Among the most frequently mentioned, several islands, peninsulas and shallows connected to the mythical plots are pointed out, as well as the lake itself. According to the folklore analyzed in the article, the lake had an important role in human life, while certain motives related to the pre-Christian religion (including the sunken church, the Queen of the lake, the souls residing at the bottom of the lake, etc.) allow one to conclude that from the ancient times, the Plateliai Lake was perceived as an important mythical place.